Dialectic of National Culture and Universal Values: Historical Roots and Modern Interpretation - Ikrom Bobokulovich Mirzayev (Scientific Trends, 2025)
This article analyzes the historical roots of national culture and universal values, as well as the processes of their mutual harmonization in the modern era. The dialectical unity of nationality and universality is considered as one of the main factors of cultural development, and the scientific foundations of the realization of national identity and integration with world civilization are revealed.
Keywords: Culture, nationality, universal values, historical roots, dialectics, globalization, harmonization.